Knowledge, awareness, and practices for prevention of Vietnamese students in the passion of COVID-19: A survey in the health industry, Nguyen Tat Thanh University, Ho Chi Minh City - Phuong, Nguyen Thi Thuy; Thuy, Phan Bui Gia; Phi, Nguyen Tran Ngoc; Nhan, Pham Nguyen Trong; Son, Nguyen Hoang (International research journal of management, IT and social sciences, 2021)
The COVID-19 pandemic is the largest viral pandemic of the 21st century. We aimed to study COVID-19 knowledge, awareness, and practices (KAP) among medical and health sciences students in the Viet Nam, survey in the health industry, Nguyen Tat Thanh University, Ho Chi Minh city. It was conducted in English and comprised two parts: socio-demographic characteristics, and KAP towards COVID-19. A total of 1370 students responded to the survey. Out of which 74,8% of female students, 25,2% of male students. The knowledge of the students on COVID-19 was of high level; however, more than one-third of them feel unconcerned about how they feel about the disease. The majority of students believe and are willing to support and follow recommendations from competent authorities in Vietnam to prevent the entry of the coronavirus. Besides, more than two-thirds of students said that they completely know how to protect themselves from the coronavirus. Students of Vietnam's health sector had an acceptable level of knowledge, awareness, and good practices of preventive measures regarding the COVID-19 virus. There were no significant differences in most categories of students' gender-related knowledge, perceptions, and practices, or years of study.